Adaptive current differential protection for active distribution network considering time synchronization error. (September 2022) - Zhou, Chenghan; Zou, Guibin; Du, Xiaogong; Zang, Lindong
Highlights: Current differential protection based on fault data self-synchronization algorithm can reduce ADN protection cost. When starting delays of relays on both sides are inconsistent, it will cause time synchronization error. When a high resistance fault occurs on the feeder with IBDG, time synchronization error will increase. Large time synchronization error will cause misjudgment of traditional current differential protection. Improved adaptive current differential protection can weaken the influence of time synchronization error. Abstract: To solve the impact of the integration of distributed generations on distribution network protection, current differential protection is introduced into the active distribution networks. Using fault data self-synchronization algorithm to construct current differential protection can reduce the cost of protection and communication, but the unsynchronized starting of relays on both sides will cause time synchronization errors and affect the reliability of protection, especially when high resistance faults occur at feeders with inverter-based DGs. In this paper, the cause of the starting delays of protective relays is analyzed through assumptions and approximations. On this basis, an adaptive current differential protection method for active distribution networks is proposed. This method uses the current amplitude ratio on both sides of the protected feeder to adaptively modify restraint current in differential protection, which can weaken the effect of time synchronization error caused by fault data self-synchronization algorithm and improve the performance of current differential protection. Finally, the effectiveness of the proposed method is verified in both PSCAD/EMTDC simulation and a closed-loop test platform based on the real-time digital simulator.